8+5x-1-3x=2x+3+3x+1-4x

Simple and best practice solution for 8+5x-1-3x=2x+3+3x+1-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+5x-1-3x=2x+3+3x+1-4x equation:


Simplifying
8 + 5x + -1 + -3x = 2x + 3 + 3x + 1 + -4x

Reorder the terms:
8 + -1 + 5x + -3x = 2x + 3 + 3x + 1 + -4x

Combine like terms: 8 + -1 = 7
7 + 5x + -3x = 2x + 3 + 3x + 1 + -4x

Combine like terms: 5x + -3x = 2x
7 + 2x = 2x + 3 + 3x + 1 + -4x

Reorder the terms:
7 + 2x = 3 + 1 + 2x + 3x + -4x

Combine like terms: 3 + 1 = 4
7 + 2x = 4 + 2x + 3x + -4x

Combine like terms: 2x + 3x = 5x
7 + 2x = 4 + 5x + -4x

Combine like terms: 5x + -4x = 1x
7 + 2x = 4 + 1x

Solving
7 + 2x = 4 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
7 + 2x + -1x = 4 + 1x + -1x

Combine like terms: 2x + -1x = 1x
7 + 1x = 4 + 1x + -1x

Combine like terms: 1x + -1x = 0
7 + 1x = 4 + 0
7 + 1x = 4

Add '-7' to each side of the equation.
7 + -7 + 1x = 4 + -7

Combine like terms: 7 + -7 = 0
0 + 1x = 4 + -7
1x = 4 + -7

Combine like terms: 4 + -7 = -3
1x = -3

Divide each side by '1'.
x = -3

Simplifying
x = -3

See similar equations:

| 3(x+8)-3x=-2(-4x+2) | | y(2/y) | | 15-6x=5-8x | | -3(x+6)+5=7(x+4)+1 | | 41/28=7/x | | 3a+9-a+8= | | 7(x-4)+8=3(x-4) | | 112-x=161 | | 12-2c=c | | 2x^2-4kx+3=0 | | 7x+7(-3x-11)=-161 | | -8-10=-1+7y | | -v+269=170 | | 0.9x-0.3(5-x)=3.9 | | 36x^3-4x=0 | | .50y+2.3=1.65 | | 10+9x=-22+x | | 83=-2x+5(-3x-14) | | 90=253-w | | x^4-7*2+12=0 | | -7+x+7x=41 | | 10+9x=-20+x | | x/6=-43 | | 41x=1974 | | -7-7(-4x-9)=168 | | 6z^2-7z+12=0 | | x+.06x=27120 | | 10sinx-1=0 | | 41x=1975 | | 12(x^3)=60(x^2)+75x | | 3x-13=-22 | | X(10x-7)+11(10x-7)=0 |

Equations solver categories